A Polymer/Peptide Complex‐Based Sensor Array That Discriminates Bacteria in Urine. Issue 48 (26th October 2017) - Han, Jinsong; Cheng, Haoran; Wang, Benhua; Braun, Markus Santhosh; Fan, Xiaobo; Bender, Markus; Huang, Wei; Domhan, Cornelius; Mier, Walter; Lindner, Thomas; Seehafer, Kai; Wink, Michael; et al.
Abstract: A negatively charged poly( para ‐phenyleneethynylene) (PPE) forms electrostatic complexes with four positively charged antimicrobial peptides (AMP). The AMPs partially quench the fluorescence of the PPE and discriminate fourteen different bacteria in water and in human urine by pattern‐based fluorescence recognition; the AMP‐PPE complexes bind differentially to the components of bacterial surfaces. The bacterial species and strains form clusters according to staining properties (Gram‐positive and Gram‐negative) or genetic similarity (genus, species, and strain). The identification and data treatment is performed by pattern evaluation with linear discriminant analysis (LDA) of the collected fluorescence intensity data. Abstract : Discriminated ! Electrostatic complexes formed from four cationic antimicrobial peptides (AMPs) and one anionic poly( para ‐phenylene‐ethynylene) (PPE) were examined as a new type of an array‐based sensor. The array identifies and discriminates 14 different types of bacteria according to Gram status and their genetic relationship in human urine by subjecting the obtained fluorescence response patterns to linear discriminant analysis.